Investigation of third‐order nonlinear optical properties of pyrazoline‐doped polyvinyl alcohol films. Issue 9 (16th January 2013) - Janardhana, K.; Ravindrachary, V.; Rajesh Kumar, P.C.; Ismayil,
Abstract A 2‐pyrazoline, 3‐(phenyl)‐5‐(4‐N, N‐dimethylaminophe nyl)‐1H‐2‐pyrazoline (PDAP) was synthesized and characterized by Fourier transform infrared, nuclear magnetic resonance, ultraviolet (UV)–visible, and Z‐scan techniques. The PDAP‐doped polyvinyl alcohol composite films were prepared by solvent casting method using dimethylformamide as solvent. The optical properties of the composites were studied using UV–visible, steady state fluorescence, single beam Z‐scan technique and degenerate four wave mixing (DFWM) technique. The optical constants such as band gap and optical activation energy were evaluated. The steady state fluorescence data showed both emission peak wavelengths and intensity change with PDAP‐doping level in the composites. The open aperture Z‐scan of the composite films displayed reverse saturable absorption. A self‐focusing effect was observed under closed aperture configuration and the nonlinear refractive index of the film was observed increasing with the increase of doping. The third‐order nonlinear susceptibility was compared with that obtained with picoseconds pulses through DFWM technique. The thermogravimetry analysis shows that the composites are thermally stable up to 260°C. POLYM. ENG. SCI., 2013. © 2013 Society of Plastics Engineers